Particle adhesion resistant polyolefin elastomer and production method thereof

By using polyethylene glycol, stearate and polydimethylsiloxane as anti-blocking agents in polyolefin elastomers, the problem of bonding blocks of POE particles is solved, and the effect of improving production efficiency and reducing costs is achieved. .

CN119307035AInactive Publication Date: 2025-01-14XINJIANG DUSHANZI PETROCHEMICAL CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411846817.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyolefin elastomer POE product particles are prone to sticking and agglomerating during transportation and storage, resulting in reduced production efficiency and increased costs. It is difficult for the prior art to effectively solve this problem.

Method used

Using polyethylene glycol, stearate and polydimethylsiloxane as anti-blocking agents, the anti-particle bonded polyolefin elastomer with a durable protective layer is formed to avoid Adhesion between particles.

Benefits of technology

It effectively avoids the adhesion and agglomeration problems of POE particles during storage or transportation, improves production efficiency, reduces labor costs, and meets the processing requirements of photovoltaic film and plastic modification enterprises.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a particle adhesion resistant polyolefin elastomer and a production method thereof, and belongs to the technical field of petrochemical industry. The polyolefin elastomer capable of resisting particle adhesion is prepared from the following raw materials: a polyolefin elastomer, an anti-adhesion agent and an antioxidant, the anti-blocking agent is prepared from the following components in percentage by mass: 20 to 60 percent of polyethylene glycol, 4 to 20 percent of stearate and 30 to 76 percent of polydimethylsiloxane, and the mass content of the polyethylene glycol is 20 to 60 percent, the mass content of the stearate is 4 to 20 percent and the mass content of the polydimethylsiloxane is 30 to 76 percent; the mass ratio of the polyolefin elastomer to the anti-blocking agent is 1000: 0.1 to 8. According to the invention, polyethylene glycol, stearate and polydimethylsiloxane are adopted as anti-blocking agents, and under the synergistic effect of the three anti-blocking agents, a protective layer with durability is formed on the surfaces of polyolefin elastomer particles, so that mutual adhesion among the particles is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petrochemical industry and relates to a polyolefin elastomer capable of resisting particle adhesion and a production method thereof. Background Art

[0002] Polyolefin elastomer (POE for short) is a product formed by copolymerization of ethylene and α-olefin (usually 1-butene, 1-hexene, 1-octene, etc.), and the content of the comonomer is usually more than 20%. Due to the high content of the comonomer used in the copolymerization reaction, which is much higher than the comonomer used in the preparation of conventional polyolefin resins, the α-olefin greatly weakens the crystalline region of the carbon-carbon main chain during the copolymerization reaction, forming an amorphous structure similar to rubber elasticity. Therefore, polyolefin elastomer products have excellent optical properties, mechanical properties, and processing properties. The transmittance, elongation at break, and low-temperature brittleness of the products are better than those of general polyethylene and polypropylene. Polyolefin elastomer products are often used in the production of photovoltaic films, automotive material modification, foaming, and electrical material modification.

[0003] Foreign petrochemical companies with commercialized POE products include Dow Chemical, ExxonMobil, Mitsui Chemicals, Sabic, SK, and LG Chem. Among them, Dow Chemical and ExxonMobil rank first in the world in POE production capacity, both at 750,000 tons. However, since ExxonMobil's propylene-based elastomers and vinyl elastomers are produced using the same set of equipment, Dow Chemical has the highest market volume of vinyl elastomer products in the world. In 2023, Dow's domestic imports will be around 400,000 tons, accounting for about 47% of the total domestic POE. Following closely behind are Japan's Mitsui, South Korea's SK, and Saudi Arabia's basic POE production capacity, which are all expanding.

[0004] Under the current situation of high profits of POE products and structural overcapacity of general products, nearly 20 domestic enterprises have planned or invested in the construction of POE production facilities. Among them, PetroChina Dushanzi Petrochemical, Hainan Beiouyi Technology Co., Ltd., and Wanhua Chemical have made the fastest progress. PetroChina Dushanzi Petrochemical has launched commercial products to the market, Hainan Beiouyi Technology Co., Ltd. and Wanhua Chemical have each provided a batch of solution products to the market, and their application performance has been basically recognized by customers.

[0005] Whether it is a foreign petrochemical enterprise or a newly entered domestic R&D company, they will encounter the problem of particle (or granule) adhesion during the POE R&D and production process. Due to the high comonomer content and low density in POE products, although POE products are shipped in the form of particles, the product particles are similar to rubber particles, and there will be problems of particle adhesion and agglomeration during transportation and storage. Especially in the hot summer, transportation in the closed space of train vans, direct sunlight when cars are queued for unloading, and stacking of pallets will cause POE particles to adhere to varying degrees. Although some companies have temporarily reduced the storage conditions of POE by renting cold storage, the high cost has not completely solved the problem of particle adhesion.

[0006] The adhesion of POE particles brings many production problems to photovoltaic film and plastic modification companies. For example, the particles after adhesion will cause inaccurate material discharge from the metering scale, the performance of the product will fluctuate from time to time, or the bridging of the material discharge will easily lead to interruption of the screw feeding. The production company needs to crush the raw materials and restart the machine, which reduces production efficiency and increases labor costs.

[0007] A Chinese patent document with authorization announcement number CN105566742B discloses a method for preparing a polyolefin alloy. The method uses a spherical high-efficiency supported Ziegler-Natta catalyst with magnesium chloride as a carrier to synthesize a polyolefin alloy in the form of nearly spherical or regular spherical particles with a diameter of 0.5 to 2 mm. The particles have good fluidity. During the polymerization process, there is no adhesion or agglomeration between the particles, and there is no problem of particles adhering to the reactor wall.

[0008] The Chinese patent document with authorization announcement number CN104448520B discloses a polyolefin insulation material and its preparation method and use, which has good mechanical properties and good electrical properties. The biggest advantage is that the insulation layer is evenly cross-linked, has excellent temperature resistance, prevents cable adhesion, and has good anti-pre-cross-linking effect; under high-speed wire pay-off, the cable surface has no melt fracture and is smooth, which is more suitable for low-smoke halogen-free flame-retardant cables with high temperature resistance, high cable surface requirements, and thin insulation layer.

[0009] A Chinese patent document with authorization announcement number CN117183158B discloses a polyolefin resin feeding device and a feeding method thereof. The method sets a flow-increasing filter element. When the suction pipe sucks the resin powder in the aggregate tank, the agglomerated powder can be filtered through the truncated cone filter ring plate, so that the agglomerated powder is located on the top of the truncated cone filter ring plate. Under the influence of the negative pressure in the suction pipe, the powder in the normal state will pass through the truncated cone filter ring plate and enter the suction pipe. The operation of the first motor can rotate the truncated cone filter ring plate relative to the aggregate tank, so that the powder in the aggregate tank is shaken to a certain extent, thereby increasing the fluidity of the powder in the aggregate tank and ensuring the continuity of feeding.

[0010] The Chinese patent document with the authorization announcement number CN114292419B discloses a PBT anti-adhesion masterbatch and its preparation method and application. The PBT anti-adhesion masterbatch includes the following raw materials in parts by weight: 30-100 parts of PBT resin, 0.6-5 parts of barium sulfate, 0.2-2 parts of antioxidant, 0.5-5 parts of silane coupling agent, 0.2-2 parts of dispersing lubricant and 0.2-2 parts of ultraviolet absorber; wherein the average particle size of barium sulfate is 0.2-1.4 μm. The PBT anti-adhesion masterbatch has an extremely low friction coefficient and excellent anti-adhesion performance. At the same time, the PBT anti-adhesion masterbatch can also maintain a high light transmittance; therefore, the PBT anti-adhesion masterbatch can be well used in anti-adhesion PBT sheets.

[0011] A Chinese patent document with authorization announcement number CN116714335B discloses an antistatic PE film suitable for powder product packaging and a preparation method thereof. High-pressure polyethylene, linear polyethylene, metallocene polyethylene, an opening agent, a carbon nanotube grafted antistatic agent and an antioxidant are used as raw materials for an antistatic heat-sealing layer, linear polyethylene, metallocene polyethylene and a coupling agent are used as raw materials for a core layer, and high-pressure polyethylene, linear polyethylene and a thickener are used as raw materials for a corona layer. The antistatic PE film suitable for powder product packaging is made by three-layer co-extrusion blown film. The introduced polydimethylaminoethyl methacrylate and polyethylene have just the right compatibility, which effectively avoids the problems of migration, precipitation and poor durability of small molecule antistatic agents, improves the dispersibility of carbon nanotubes, and also improves the mechanical properties of the matrix. The film has excellent antistatic properties, excellent mechanical properties, and high heat-sealing strength.

[0012] However, the adhesion of polyolefin elastomer POE product particles is different from the adhesion of polymers and the adhesion during post-modification processing. It is mainly reflected in the adhesion between particles when the materials are stacked. The above-mentioned prior art improves the polymer adhesion reactor and conveying pipeline during the product polymerization process, or provides processing auxiliary equipment with a crushing effect through the design and modification of processing equipment. It involves the technology of improving the adhesion problem through additive formula design, which cannot solve the adhesion problem of polyolefin elastomer POE product particles well. Summary of the invention

[0013] In order to solve the problems existing in the prior art, the present invention provides a polyolefin elastomer with resistance to particle adhesion and a production method thereof, so as to improve the problem of POE particle adhesion and agglomeration in the prior art.

[0014] In a first aspect, the present invention provides a polyolefin elastomer having resistance to particle adhesion. The raw materials for preparing the polyolefin elastomer having resistance to particle adhesion include a polyolefin elastomer and a processing aid, wherein: The processing aids include antioxidants and anti-adhesive agents; the anti-adhesive agents include polyethylene glycol, stearate and polydimethylsiloxane, wherein the mass content of polyethylene glycol is 20 wt% to 60 wt%, the mass content of stearate is 4 wt% to 20 wt%, and the mass content of polydimethylsiloxane is 30 wt% to 76 wt%; The mass ratio of the polyolefin elastomer to the anti-blocking agent is 1000:0.1 to 8.

[0015] As an optional embodiment, the density of the polyolefin elastomer is 0.855 g / cm 3 Up to 0.890 g / cm 3 .

[0016] As an optional embodiment, the number average molecular weight Mn of the polyolefin elastomer is 40000 g / mol to 120000 g / mol, or the weight average molecular weight Mw is 12000 g / mol to 70000 g / mol, and the molecular weight distribution index is 1.2 to 4.1.

[0017] As an optional embodiment, the polyolefin elastomer has a melt index of 0.3 to 30 g / 10 min at 190° C. and a load of 2.16 kg.

[0018] As an optional embodiment, the antioxidant includes a primary antioxidant and a secondary antioxidant.

[0019] As an optional embodiment, the primary antioxidant is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (also known as: antioxidant 1010) and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester (also known as: antioxidant 1076).

[0020] As an optional embodiment, the auxiliary antioxidant is at least one of tris(2,4-di-tert-butylphenyl)phosphite (also known as antioxidant 168) and bis(2,4-di-tert-butylphenyl)propionate] pentaerythritol diphosphite (also known as antioxidant 626).

[0021] As an optional embodiment, the mass ratio of the polyolefin elastomer to the primary antioxidant is 1000:0.1 to 4.

[0022] As an optional embodiment, the mass ratio of the polyolefin elastomer to the auxiliary antioxidant is 1000:0.1 to 3.5.

[0023] As an optional embodiment, the mass ratio of the primary antioxidant to the auxiliary antioxidant is (2 to 3): (0.8 to 5).

[0024] As an optional embodiment, in the anti-adhesion agent, the molecular weight of polyethylene glycol is 2000 g / mol to 8000 g / mol.

[0025] As an optional embodiment, the stearate is zinc stearate.

[0026] As an optional embodiment, the critical shear rate of the anti-particle adhesion polyolefin elastomer at 80° C. is 190 to 300 s -1 , amplitude is 30 MPa to 50 MPa (tested by high pressure capillary rheometer).

[0027] As an optional embodiment, the particle-adhesion resistant polyolefin elastomer has a torque difference of less than 0.2 N between 3 min and 30 min at a shear temperature of 235° C. (Haake torque rheometer test).

[0028] As an optional embodiment, when the particle-adhesion resistant polyolefin elastomer is subjected to cast film processing at a temperature of 85° C., the screw torque (or main motor torque) is 25 Nm to 60 Nm (tested by a cast film processing instrument).

[0029] In the present invention, the screw torque of the anti-particle adhesion polyolefin elastomer is obtained by testing a cast film processing instrument at a processing temperature of 85° C. During the cast film processing, the main motor drives the screw to rotate, so the torque of the screw is also the torque of the main motor.

[0030] As an optional embodiment, after the anti-particle adhesion polyolefin elastomer is sealed in a 25 kg bag and placed in a constant temperature and humidity chamber at 40°C and 50% humidity for 24 hours, the number of adhesion particles (or large particles) is less than 15 / kg (that is, take 25 kg of anti-particle adhesion polyolefin elastomer and seal it in a 25 kg packaging bag, and after placing it in a constant temperature and humidity chamber at 40°C and 50% humidity for 24 hours, the number of adhesion particles in the anti-particle adhesion polyolefin elastomer is less than 15 / kg.).

[0031] In the present invention, according to SH / T 1541.1, the particle size of the adhesion particles is greater than 5 mm, and thus, the number of particles with a particle size greater than 5 mm is counted as adhesion particles.

[0032] In a second aspect, the present invention provides a method for producing the above-mentioned anti-particle adhesion polyolefin elastomer, the production method comprising the following steps: The polyolefin elastomer and the processing aid are mixed according to a formula to obtain a mixture; the processing aid includes an antioxidant and an anti-blocking agent; The mixture is kneaded, melted and extruded into granules to obtain a polyolefin elastomer with resistance to particle adhesion.

[0033] In the present invention, based on the same inventive concept, the components and contents of the above-mentioned anti-particle adhesion polyolefin elastomer are still applicable in its production method and will not be repeatedly introduced here.

[0034] As an optional implementation, the polyolefin elastomer is a powder.

[0035] As an optional embodiment, the melt pump outlet temperature of the mixed melting is 160°C to 250°C.

[0036] As an optional implementation manner, the inlet pressure of the melt pump for mixing and melting is 1 MPa to 4 MPa.

[0037] As an optional embodiment, the pressure difference before and after the molten mixing screen is 1.5 MPa to 8.4 MPa.

[0038] As an optional embodiment, the water temperature of the granules during extrusion granulation is 10°C to 60°C.

[0039] In the present invention, the above technical features can be freely combined to form a new technical solution without conflicting with each other.

[0040] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects: (1) The present invention uses polyethylene glycol, zinc stearate, and polydimethylsiloxane as anti-adhesive agents, wherein polyethylene glycol and zinc stearate are molecules with relatively low polarity and have good compatibility with POE; polydimethylsiloxane has a relatively low surface tension, which helps to destroy the foam generated during the use of polyethylene glycol, and can play a defoaming role, thereby avoiding the generation of voids or stress white spots during the POE extrusion granulation process; the anti-adhesive agent can be precipitated onto the surface of the particles during the granulation shearing process; therefore, under the synergistic effect of polyethylene glycol, zinc stearate, and polydimethylsiloxane, a durable protective layer can be formed on the POE particles to avoid mutual adhesion between the particles; (2) The anti-particle adhesion polyolefin elastomer prepared by the method of the present invention can effectively avoid the adhesion of POE particles during storage or transportation, and will not cause agglomeration even if piled for a long time, which brings convenience to the storage and application of raw materials; it can solve the derivative problems caused by particle adhesion to photovoltaic film and plastic modification companies, such as inaccurate material discharge from metering scales, material bridging leading to interruption of screw feeding, and the need for production companies to crush raw materials, increasing labor costs, etc. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] In order to facilitate transportation, storage and subsequent processing, metallocene polyethylene powder is usually made into pellets in an extrusion granulator through mixing, extrusion, pelletizing and other processes. For conventional polyethylene, its density is high and the viscosity of the molten material is low. Therefore, when extruding and pelletizing, there is no need to add any anti-adhesive agent. The material has good rigidity and the polyethylene pellets will not stick together after cooling. The density of polyolefin elastomer (0.855g / cm 3 Up to 0.890g / cm 3 ) is low and has a low melting point. Therefore, conventional polyethylene granulation conditions are used to produce polyolefin elastomer POE. The produced POE particles have severe adhesion between particles, many tailing particles, and a lot of debris. The packaged particles cannot be used by downstream customers.

[0043] To this end, the inventors intend to provide a method for producing a polyolefin elastomer that is resistant to particle adhesion. First, polyethylene glycol is introduced as an anti-adhesion agent, and the molecular weight of the introduced polyethylene glycol is controlled to be 2000 g / mol to 8000 g / mol to avoid degradation and yellowing caused by the use of low molecular weight polyethylene glycol; secondly, the extrusion granulation production method is used to synergistically solve the problems of many tailing particles and more debris, so that the POE particles meet the processing requirements of downstream customers.

[0044] In addition, the inventors found that due to the large surface tension of polyethylene glycol, bubbles are easily generated during the extrusion granulation and pelletizing and transportation process, which increases the possibility of bubbles, voids and white spots in POE particles. Therefore, by utilizing the synergistic effect of additives, polydimethylsiloxane is innovatively added as a defoaming agent to eliminate the problems of bubbles, voids and white spots that occur during the application of polyethylene glycol, thus making up for the application shortcomings of polyethylene glycol.

[0045] Some embodiments of the present invention provide a polyolefin elastomer with resistance to particle adhesion. The raw materials for preparing the polyolefin elastomer with resistance to particle adhesion include a polyolefin elastomer and a processing aid, wherein: The processing aid includes an antioxidant and an anti-blocking agent; the anti-blocking agent includes polyethylene glycol, stearate and polydimethylsiloxane, wherein the mass content of polyethylene glycol is 20 wt% to 60 wt% (for example, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 50 wt% or 55 wt%), the mass content of stearate is 4 wt% to 20 wt% (for example, 5 wt%, 10 wt%, 12 wt%, 15 wt%, 17 wt% or 19 wt%), and the mass content of polydimethylsiloxane is 30 wt% to 76 wt% (for example, 35 wt%, 40 wt%, 35 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt% or 75 wt%); The mass ratio of the polyolefin elastomer to the anti-blocking agent is 1000:0.1 to 8 (eg, 1000:0.5, 1000:1, 1000:2, 1000:3, 1000:4, 1000:5, 1000:6 or 1000:7).

[0046] In some embodiments, the density of the polyolefin elastomer is 0.855 g / cm 3 Up to 0.890g / cm 3 , a number average molecular weight Mn of 40,000 g / mol to 120,000 g / mol, or a weight average molecular weight Mw of 12,000 g / mol to 70,000 g / mol, and a molecular weight distribution index of 1.2 to 4.1; and a melt index of the polyolefin elastomer at 190° C. and 2.16 kg load of 0.3 g / 10 min to 30 g / 10 min.

[0047] In some embodiments, the antioxidant includes a primary antioxidant and a secondary antioxidant; the primary antioxidant is at least one of antioxidant 1010 and antioxidant 1076; the secondary antioxidant is at least one of antioxidant 168 and antioxidant 626; the mass ratio of the polyolefin elastomer to the primary antioxidant is 1000:0.1 to 4 (for example, 1000:0.5, 1000:1, 1000:1.5, 1000:2, 1000:2.5, 1000:3 or 1000:3.5), and the mass ratio to the secondary antioxidant is 1000:0.1 to 3.5 (for example, 1000:0.5, 1000:1, 1000:1.5, 1000:2, 1000:2.5, 1000:3 or 1000:3.2).

[0048] In some embodiments, the mass ratio of the primary antioxidant to the secondary antioxidant is (2 to 3):(0.8 to 5) (e.g., (2 to 3):1, (2 to 3):2, (2 to 3):3, (2 to 3):4 or (2 to 3):4.5).

[0049] In some embodiments, in the anti-adhesive agent, the molecular weight of polyethylene glycol is 2000 g / mol to 8000 g / mol.

[0050] In some embodiments, the stearate is zinc stearate.

[0051] In some embodiments, the critical shear rate of the particle-resistant polyolefin elastomer at 80° C. is 190 to 300 s -1 (For example, 200 s -1 , 220 s -1 , 250 s -1 , 260 s -1 or 280 s -1 ), with an amplitude (tested using a high pressure capillary rheometer) of 30 MPa to 50 MPa (e.g., 32 MPa, 35 MPa, 40 MPa, 45 MPa, or 48 MPa).

[0052] In some embodiments, the difference in torque between 3 min and 30 min of the anti-particle adhesion polyolefin elastomer at a shear temperature of 235° C. is less than 0.2 N (Haake torque rheometer test); when the anti-particle adhesion polyolefin elastomer is subjected to cast film processing at a temperature of 85° C., the screw torque (tested by a cast film processor) is between 25 Nm and 60 Nm (for example, 30 Nm, 40 Nm, 50 Nm or 55 Nm).

[0053] In some embodiments, after the particle-adhesion-resistant polyolefin elastomer is sealed in a 25 kg bag in a constant temperature and humidity chamber at 40° C. and 50% humidity for 24 hours, the number of adhering particles (or large particles) is less than 15 / kg.

[0054] In the present invention, according to SH / T 1541.1, the particle size of the adhesion particles is greater than 5 mm, and thus, the number of particles with a particle size greater than 5 mm is counted as adhesion particles.

[0055] Some embodiments of the present invention also provide a method for preparing any of the above-mentioned anti-particle adhesion polyolefin elastomers, comprising the following steps: The polyolefin elastomer and the processing aid are mixed according to a formula to obtain a mixture; the processing aid includes an antioxidant and an anti-blocking agent; The mixture is kneaded, melted and extruded into granules to obtain a polyolefin elastomer with resistance to particle adhesion.

[0056] In some embodiments, the polyolefin elastomer is in the form of a powder.

[0057] In some embodiments, the melt pump outlet temperature of the mixed melt is 160°C to 250°C (e.g., 180°C, 200°C, 210°C, 220°C, 230°C, or 240°C), the melt pump inlet pressure of the mixed melt is 1 MPa to 4 MPa (e.g., 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, or 3.8 MPa), and the pressure difference before and after the mixed melt screen is 1.5 MPa to 8.4 MPa (e.g., 2 MPa, 3 MPa, 5 MPa, 6 MPa, 7 MPa, or 8 MPa).

[0058] In some embodiments, the granulation water temperature of the extrusion granulation is 10°C to 60°C (eg, 20°C, 30°C, 40°C, or 50°C).

[0059] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0060] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0061] Specifically, the present invention uses a high-pressure capillary rheometer to test the critical shear rate of the polyolefin elastomer at 80° C., uses a Haake torque rheometer to test the torque of the polyolefin elastomer, and uses a cast film processor to test the torque of the polyolefin elastomer.

[0062] Example 1 A polyolefin elastomer with anti-particle adhesion is prepared by using the following raw materials: POE powder; the density of the POE powder is 0.886 g / cm 3 , the number average molecular weight Mn is 51000 g / mol, the weight average molecular weight Mw is 65000 g / mol, the molecular weight distribution index is 2.2, and the melt index at 190℃ and 2.16 kg load is 0.8 g / 10 min; Anti-adhesive agent; the anti-adhesive agent is a mixture of polyethylene glycol with a molecular weight of 3000 g / mol, zinc stearate and polydimethylsiloxane, and the amount of the anti-adhesive agent added is 1000 mg / kg POE powder (i.e., 1000 mg of the anti-adhesive agent is added per kg POE powder); wherein the mass content of polyethylene glycol in the anti-adhesive agent is 25wt%, the mass content of zinc stearate in the anti-adhesive agent is 10wt%, and the mass content of polydimethylsiloxane in the anti-adhesive agent is 65wt%; Antioxidant; the antioxidant comprises a primary antioxidant 1010 and an auxiliary antioxidant 168, wherein the primary antioxidant 1010 is added in an amount of 400 mg / kg POE powder, and the auxiliary antioxidant 168 is added in an amount of 200 mg / kg POE powder.

[0063] The method for producing the particle-resistant polyolefin elastomer comprises the following steps: POE powder, anti-blocking agent and antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain the target product, wherein the outlet temperature of the extruder mixing, melting and melting pump is 180°C, the inlet pressure of the extruder mixing, melting and melting pump is 4.0 MPa, the pressure difference before and after the screen of the molten material is 1.8 MPa, and the temperature of the granule water (also called pelletizing water) for extrusion granulation is 12°C.

[0064] The particle-adhesion-resistant polyolefin elastomer (abbreviated as anti-adhesion POE) prepared in this embodiment has a critical shear rate of 260 s at 80°C for high pressure capillary rheology melt. -1 , amplitude is 45 MPa; the torque difference between 3 min and 30 min of anti-adhesion POE at 235℃ shear temperature was measured by Haake torque rheometer, which was 0.18 N; the main torque of anti-adhesion POE was 40 Nm at 85℃ processing temperature measured by cast film processor.

[0065] The anti-adhesive POE particles obtained by extrusion granulation were packed in 25 kg bags and placed in a constant temperature and humidity chamber at 40°C and 50% humidity for 24 hours. The number of adhering particles of the anti-adhesive POE was 3 / kg, and the number of bubbles, voids, and white spot particles was 0.

[0066] Example 2 A polyolefin elastomer with anti-particle adhesion is prepared by using the following raw materials: POE powder; the density of the POE powder is 0.875 g / cm 3 , the number average molecular weight Mn is 42000 g / mol, the weight average molecular weight Mw is 60000 g / mol, the molecular weight distribution index is 2.3, and the melt index at 190℃ and 2.16 kg load is 5 g / 10 min; Anti-adhesive agent; the anti-adhesive agent is a mixture of polyethylene glycol with a molecular weight of 4500 g / mol, zinc stearate and polydimethylsiloxane, and the amount of the anti-adhesive agent added is 3000 mg / kg POE powder; wherein the mass content of polyethylene glycol in the anti-adhesive agent is 5wt5%, the mass content of zinc stearate in the anti-adhesive agent is 5wt%, and the mass content of polydimethylsiloxane in the anti-adhesive agent is 40wt%; Antioxidant; the antioxidant includes a primary antioxidant 1076 and an auxiliary antioxidant 626, wherein the primary antioxidant 1076 is added in an amount of 2000 mg / kg POE powder, and the auxiliary antioxidant 626 is added in an amount of 1500 mg / kg POE powder.

[0067] The method for producing the particle-resistant polyolefin elastomer comprises the following steps: POE powder, anti-blocking agent and antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain the target product, wherein the outlet temperature of the extruder mixing, melting and melting pump is 200°C, the inlet pressure of the extruder mixing, melting and melting pump is 2.5 MPa, the pressure difference before and after the screen of the molten material is 3 MPa, and the water temperature of the extruded granulated particles is 30°C.

[0068] The particle-adhesion-resistant polyolefin elastomer (abbreviated as anti-adhesion POE) prepared in this embodiment has a critical shear rate of 250 s at 80°C for high pressure capillary rheology melt. -1 , amplitude is 40 MPa; the torque difference between 3 min and 30 min of anti-adhesion POE at 235℃ shear temperature was measured by Haake torque rheometer, which was 0.12 N; the main torque of anti-adhesion POE was 32 Nm at 85℃ processing temperature measured by cast film processor.

[0069] The anti-adhesive POE particles obtained by extrusion granulation were packed in 25 kg bags and placed in a constant temperature and humidity chamber at 40°C and 50% humidity for 24 hours. The number of adhering particles of the anti-adhesive POE was 1 / kg, and the number of bubbles, voids, and white spot particles was 0.

[0070] Example 3 A polyolefin elastomer with anti-particle adhesion is prepared by using the following raw materials: POE powder; the density of the POE powder is 0.860 g / cm 3 , the number average molecular weight Mn is 41000 g / mol, the weight average molecular weight Mw is 50000 g / mol, the molecular weight distribution index is 2.2, and the melt index at 190℃ and 2.16 kg load is 14 g / 10 min; Anti-adhesive agent; the anti-adhesive agent is a mixture of polyethylene glycol with a molecular weight of 7000 g / mol, zinc stearate and polydimethylsiloxane, and the amount of the anti-adhesive agent added is 4500 mg / kg POE powder; wherein the mass content of polyethylene glycol in the anti-adhesive agent is 40wt%, the mass content of zinc stearate in the anti-adhesive agent is 15wt%, and the mass content of polydimethylsiloxane in the anti-adhesive agent is 45wt%; Antioxidant; the antioxidant includes a primary antioxidant 1076 and an auxiliary antioxidant 168, wherein the primary antioxidant 1076 is added in an amount of 3000 mg / kg POE powder, and the auxiliary antioxidant 168 is added in an amount of 3500 mg / kg POE powder.

[0071] The method for producing the particle-resistant polyolefin elastomer comprises the following steps: POE powder, anti-blocking agent and antioxidant are added into the extruder barrel according to the above formula for mixing, melting and extrusion granulation to obtain the target product, wherein the outlet temperature of the extruder mixing, melting and melting pump is 230°C, the inlet pressure of the extruder mixing, melting and melting pump is 1.2 MPa, the pressure difference before and after the screen of the molten material is 4.7 MPa, and the water temperature of the extruded granulated particles is 55°C.

[0072] The particle-adhesion-resistant polyolefin elastomer (abbreviated as anti-adhesion POE) prepared in this embodiment has a critical shear rate of 200 s at 80°C for high pressure capillary rheology melt. -1 , amplitude is 33 MPa; the torque difference between 3 min and 30 min of anti-adhesion POE at 235℃ shear temperature was measured by Haake torque rheometer, which was 0.09 N; the main torque of anti-adhesion POE was measured at 85℃ processing temperature by cast film processing instrument, which was 28 Nm.

[0073] The anti-adhesive POE particles obtained by extrusion granulation were packed in 25 kg bags and placed in a constant temperature and humidity chamber at 40°C and 50% humidity for 24 hours. The number of adhering particles of the anti-adhesive POE was 0 / kg, and the number of bubbles, voids, and white spot particles was 0.

[0074] Comparative Example 1 A composite polyolefin elastomer is prepared using the following raw materials: POE powder; the density of the POE powder is 0.886 g / cm 3 , the number average molecular weight Mn is 51000 g / mol, the weight average molecular weight Mw is 60000 g / mol, the molecular weight distribution index is 2.2, and the melt index at 190℃ and 2.16 kg load is 0.8 g / 10 min; Antioxidant; the antioxidant comprises a primary antioxidant 1010 and an auxiliary antioxidant 168, wherein the primary antioxidant 1010 is added in an amount of 400 mg / kg POE powder, and the auxiliary antioxidant 168 is added in an amount of 200 mg / kg POE powder.

[0075] The method for producing the particle-resistant polyolefin elastomer comprises the following steps: POE powder and antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain composite POE, wherein the outlet temperature of the extruder mixing, melting and melting pump is 180°C, the inlet pressure of the extruder mixing, melting and melting pump is 4.1 MPa, the pressure difference before and after the screen of the molten material is 1.8 MPa, and the water temperature of the extruded granulated particles is 12°C.

[0076] The composite polyolefin elastomer (abbreviated as composite POE) prepared in this comparative example has a critical shear rate of 263 s at 80°C for high pressure capillary rheology melt. -1 , amplitude is 47 MPa; the torque difference between 3 min and 30 min of anti-adhesion POE at 235℃ shear temperature was measured by Haake torque rheometer, which was 0.19 N; the main torque of anti-adhesion POE was 42 Nm at 85℃ processing temperature measured by cast film processor.

[0077] The composite POE particles obtained by extrusion granulation were packed in 25 kg bags and placed in a constant temperature and humidity chamber at 40°C and 50% humidity for 24 hours. The number of sticky particles of the anti-sticking POE was 78 / kg, and the number of bubbles, voids, and white spot particles was 0.

[0078] Comparative Example 2 A polyolefin elastomer with anti-particle adhesion is prepared by using the following raw materials: POE powder; the density of the POE powder is 0.875 g / cm 3 , the number average molecular weight Mn is 42000 g / mol, the weight average molecular weight Mw is 55000 g / mol, the molecular weight distribution index is 2.3, and the melt index at 190℃ and 2.16 kg load is 5 g / 10 min; Anti-adhesive agent; the anti-adhesive agent is a mixture of polyethylene glycol with a molecular weight of 4500 g / mol, zinc stearate and polydimethylsiloxane, and the amount of the anti-adhesive agent added is 3000 mg / kg POE powder; wherein the mass content of polyethylene glycol in the anti-adhesive agent is 55wt%, the mass content of zinc stearate in the anti-adhesive agent is 5wt%, and the mass content of polydimethylsiloxane in the anti-adhesive agent is 40wt%; Antioxidant; the antioxidant includes a primary antioxidant 1076 and an auxiliary antioxidant 626, wherein the primary antioxidant 1076 is added in an amount of 2000 mg / kg POE powder, and the auxiliary antioxidant 626 is added in an amount of 1500 mg / kg POE powder.

[0079] The method for producing the particle-resistant polyolefin elastomer comprises the following steps: POE powder, anti-blocking agent and antioxidant are added into the extruder barrel according to the above formula for mixing, melting and extrusion granulation to obtain the target product, wherein the outlet temperature of the extruder mixing, melting and melting pump is 252°C, the inlet pressure of the extruder mixing, melting and melting pump is 0.5 MPa, the pressure difference before and after the screen of the molten material is 1 MPa, and the water temperature of the extruded granulated particles is 65°C.

[0080] The anti-particle adhesion polyolefin elastomer (abbreviated as anti-adhesion POE) prepared in this comparative example has a critical shear rate of 248 s at 80°C for high pressure capillary rheology melt. -1 , amplitude is 39 MPa; the torque difference between 3 min and 30 min of anti-adhesion POE at 235℃ shear temperature was measured by Haake torque rheometer, which was 0.15 N; the main torque of anti-adhesion POE was 33 Nm at 85℃ processing temperature measured by cast film processor.

[0081] The anti-adhesive POE particles obtained by extrusion granulation were packed in 25 kg bags and placed in a constant temperature and humidity chamber at 40°C and 50% humidity for 24 hours. The number of adhering particles of the anti-adhesive POE was 54 / kg.

[0082] Comparative Example 3 A polyolefin elastomer with anti-particle adhesion is prepared by using the following raw materials: POE powder; the density of the POE powder is 0.860 g / cm 3 , the number average molecular weight Mn is 41000 g / mol, the weight average molecular weight Mw is 50000 g / mol, the molecular weight distribution index is 2.2, and the melt index at 190℃ and 2.16 kg load is 14 g / 10 min; Anti-adhesive agent; the anti-adhesive agent is a mixture of polyethylene glycol with a molecular weight of 7000 g / mol and zinc stearate, and the amount of the anti-adhesive agent added is 2475 mg / kg POE powder; wherein the mass content of polyethylene glycol in the anti-adhesive agent is 72.7wt%, and the mass content of zinc stearate in the anti-adhesive agent is 27.3wt%; Antioxidant; the antioxidant includes a primary antioxidant 1076 and an auxiliary antioxidant 168, wherein the primary antioxidant 1076 is added in an amount of 3000 mg / kg POE powder, and the auxiliary antioxidant 168 is added in an amount of 3500 mg / kg POE powder. The method for producing the anti-particle adhesion polyolefin elastomer comprises the following steps: POE powder, anti-blocking agent and antioxidant are added into the barrel of the extruder according to the above formula for mixing, melting and extrusion granulation to obtain the target product, wherein the outlet temperature of the extruder mixing, melting and melting pump is 230°C, the inlet pressure of the extruder mixing, melting and melting pump is 1.3 MPa, the pressure difference before and after the screen of the molten material is 4.6 MPa, and the water temperature of the extruded granulated particles is 55°C.

[0083] The particle-resistant polyolefin elastomer (anti-sticking POE) prepared in this comparative example has a critical shear rate of 196 s at 80°C for its high-pressure capillary rheology melt. -1 , amplitude is 30 MPa; the torque difference between 3 min and 30 min of POE at a shear temperature of 235°C was measured by a Haake torque rheometer, which was 0.08 N; the main engine torque of POE was measured at a processing temperature of 85°C by a cast film processor, which was 27 Nm.

[0084] The POE particles obtained by extrusion granulation were packed in 25 kg bags and placed in a constant temperature and humidity chamber at 40°C and 50% humidity for 24 hours before testing the adhesion performance. The number of adhesion particles of the POE was 5 / kg, and the number of bubbles, voids, and white spot particles was 66 / kg.

[0085] The target product particles prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1.

[0086] It can be seen from Table 1 that the anti-adhesion POE particles prepared by the method provided in Examples 1 to 3 of the present invention have significantly reduced number of adhesion particles, and there are no bubbles, voids and white spot particles, while the POE prepared by the method provided in Comparative Examples 1 to 3 has more adhesion particles, or more bubbles, voids and white spot particles.

[0087] Table 1 .

[0088] Specifically, compared with Example 1, Comparative Example 1 did not add an anti-blocking agent (ie, a mixture of polyethylene glycol, zinc stearate and polydimethylsiloxane) when preparing POE, resulting in a larger number of sticky particles in the POE target product in the adhesion performance test.

[0089] Compared with Example 2, when preparing POE, the process parameters of mixing melting and extrusion granulation in Comparative Example 2 are higher than the process parameter range of the present invention, which results in the POE target product having a larger number of adhesion particles in the adhesion performance test.

[0090] Compared with Example 3, in Comparative Example 3, no polydimethylsiloxane was added to the anti-adhesive raw material when preparing POE, resulting in a larger number of bubbles, voids, and white spot particles in the POE target product. This indicates that the polydimethylsiloxane in the anti-adhesive agent can be used as a defoaming agent in the mixing, melting and extrusion granulation production process of POE, eliminating the problems of bubbles, voids and white spots that occur during the application of polyethylene glycol, and making up for the application shortcomings of polyethylene glycol.

[0091] In summary, the present invention adopts polyethylene glycol, zinc stearate, and polydimethylsiloxane as anti-adhesive agents, wherein polyethylene glycol and zinc stearate have good compatibility with POE; polydimethylsiloxane has a low surface tension, which helps to destroy the foam generated during the use of polyethylene glycol, and can play a defoaming role, thereby avoiding the generation of voids or stress white spots during the POE extrusion granulation process; the anti-adhesive agent can be precipitated onto the particle surface during the granulation shear process; therefore, under the synergistic effect of polyethylene glycol, zinc stearate and polydimethylsiloxane, a durable protective layer can be formed on the POE particles to avoid mutual adhesion between particles.

Claims

1. A polyolefin elastomer having an anti-particle adhesion property, characterized in that: The raw materials for preparing the anti-particle adhesion polyolefin elastomer include polyolefin elastomer and processing aid, wherein: The processing aids include antioxidants and anti-adhesive agents; the anti-adhesive agents include polyethylene glycol, stearate and polydimethylsiloxane, wherein the mass content of polyethylene glycol is 20 wt% to 60 wt%, the mass content of stearate is 4 wt% to 20 wt%, and the mass content of polydimethylsiloxane is 30 wt% to 76 wt%; The mass ratio of the polyolefin elastomer to the anti-blocking agent is 1000:0.1 to 8.

2. The particle-adhesion-resistant polyolefin elastomer according to claim 1, characterized in that: The polyolefin elastomer has a number average molecular weight Mn of 40000 g / mol to 120000 g / mol or a weight average molecular weight Mw of 12000 g / mol to 70000 g / mol, and a molecular weight distribution index of 1.2 to 4.

1.

3. The particle-adhesion resistant polyolefin elastomer according to claim 2, characterized in that: The density of polyolefin elastomer is 0.855 g / cm 3 Up to 0.890 g / cm 3 .

4. The particle-adhesion resistant polyolefin elastomer according to claim 3, characterized in that: The melt index of the polyolefin elastomer at 190° C. and 2.16 kg load is 0.3 g / 10 min to 30 g / 10 min.

5. The particle-adhesion resistant polyolefin elastomer according to claim 4, characterized in that: Antioxidants include primary antioxidants and secondary antioxidants; The primary antioxidant is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; The auxiliary antioxidant is at least one of tris(2,4-di-tert-butylphenyl)phosphite and bis(2,4-di-tert-butylphenyl)propionate]pentaerythritol diphosphite; The stearate is zinc stearate.

6. The particle-adhesion resistant polyolefin elastomer according to claim 5, characterized in that: The mass ratio of the polyolefin elastomer to the primary antioxidant is 1000:0.1 to 4; The mass ratio of the polyolefin elastomer to the auxiliary antioxidant is 1000:0.1 to 3.

5.

7. The particle-adhesion resistant polyolefin elastomer according to claim 6, characterized in that: The mass ratio of the primary antioxidant to the auxiliary antioxidant is 2 to 3:0.8 to 5.

8. The particle-adhesion-resistant polyolefin elastomer according to claim 7, characterized in that: In the anti-adhesive agent, the molecular weight of polyethylene glycol is 2000 g / mol to 8000 g / mol.

9. The particle-adhesion resistant polyolefin elastomer according to any one of claims 1 to 8, characterized in that The critical shear rate of anti-particle adhesion polyolefin elastomer at 80°C is 190s -1 Up to 300 s -1 , with an amplitude of 30 MPa to 50 MPa.

10. A method for producing a particle-adhesion resistant polyolefin elastomer according to any one of claims 1 to 9, characterized in that: The following steps are involved: The polyolefin elastomer and the processing aid are mixed according to a formula to obtain a mixture; the processing aid includes an antioxidant and an anti-blocking agent; The mixture is kneaded, melted and extruded into granules to obtain a polyolefin elastomer with resistance to particle adhesion.

11. The method for producing a particle-adhesion resistant polyolefin elastomer according to claim 10, characterized in that: The polyolefin elastomer is a powder.

12. The method for producing a particle-adhesion resistant polyolefin elastomer according to claim 10, characterized in that: The melt pump outlet temperature of the mixed melt is 160°C to 250°C.

13. The method for producing a particle-adhesion resistant polyolefin elastomer according to claim 12, characterized in that: The melt pump inlet pressure for mixing and melting is 1 MPa to 4 MPa.

14. The method for producing a particle-adhesion resistant polyolefin elastomer according to claim 13, characterized in that: The pressure difference before and after the sieve for mixing and melting is 1.5 MPa to 8.4 MPa.

15. The method for producing a particle-adhesion resistant polyolefin elastomer according to claim 14, characterized in that: The granule water temperature for extrusion granulation is 10°C to 60°C.

Citation Information

Patent Citations

  • A polyolefin insulating material, its preparation method and uses

    CN104448520B

  • A method for preparing a polyolefin alloy

    CN105566742B

  • A PBT anti-adhesion masterbatch and its preparation method and application

    CN114292419B

  • An antistatic PE film suitable for packaging powder products and its preparation method

    CN116714335B

  • A polyolefin resin feeding device and feeding method thereof

    CN117183158B